Pendidikan Kewirausahaan Perspektif Hadis - Fatiya Nazhifa; Citra Lianingsih; Salsa Nabila (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
Islamic entrepreneurship education integrates ethical, moral, and spiritual values with practical business practices. This study examines the perspective of the Prophet Muhammad’s hadith on entrepreneurship, emphasizing principles such as honesty, independence, creativity, risk-taking, and social responsibility. Using a qualitative approach, primary hadith sources and scholarly interpretations are analyzed to identify both values and practical implementations of entrepreneurship education in Islam. Findings reveal that the Prophet emphasized self-reliance, productive work, and ethical business conduct, providing practical guidance such as utilizing available resources, step-by-step mentoring, and progressive skill development. Additionally, Islamic entrepreneurship education prioritizes character formation, integrity, and social contribution alongside economic gain. Practical examples from hadith illustrate methods for instilling entrepreneurial values, including prohibitions against unethical transactions, encouragement to work with one’s own hands, and support for independent income generation. The study shows that integrating moral guidance from hadith with business training produces competent, responsible, and ethically grounded entrepreneurs. This framework offers a comprehensive model for modern entrepreneurship education, balancing profitability, ethical conduct, and societal welfare. The research contributes to understanding how Islamic values can form the foundation of sustainable and morally conscious business practices, providing educators and practitioners with actionable insights for cultivating entrepreneurship aligned with Islamic teachings.